Exploring seed to seed effects for understanding invasive species success - Guido, Anaclara; Hoss, Daniela; Pillar, Valério D. (Perspectives in ecology and conservation, 2017)
•Earlier germination of E. plana may explain its high invasion potential in southern Brazil.•E. plana seeds did not affect germination of native seeds in laboratory conditions.•Seeds of some native grasses delayed E. plana germination and decreased its leave and root growth.•Our results may reveal potential options for restoring invaded grasslands in southern Brazil. Comparative approaches between native and invasive species germination are useful for understanding invasion success. We studied the role of invasive–native neighboring seeds on germination and early growth of different grasses. We focused on the non-native species Eragrostis plana Ness, the most invasive plant in southern Brazilian grasslands. A germination experiment was performed with three neighboring seed treatments: (i) each species separately, (ii) interspecific seed interactions of native vs. invasive, and (iii) native vs. other native species. The experiment was conducted in a growth chamber; seeds were placed in Petri dishes and grown for 10 days. For each treatment we measured: germination percentage, germination rate index, seedling leaf and root lengths. E. plana germination was remarkably different from native grasses, 73.3% of seeds germinated within 24h. This earlier germination may explain its high invasion potential, as immediate access to limited resources enhances opportunities for establishment and growth. E. plana seeds did not significantly affect germination of other native seeds. However, we demonstrated that some native seeds delayed E. plana germination and decreased its growth. Short delays in germination and growth reduction can result in large differences in final biomass, which may have important implications for preventing E. plana invasion.